0
$\begingroup$

I got the following equation: $\cos{x}\cdot y'=y\sin {x} + \sin^2x$.

Probably a fairly simple equation. I run into problems with the integrating factor.

I get: $y'-y\tan x=\tan x\sin x$

So $g(x)=tan(x) \iff G(x)=-\ln|\cos x|+C$.

So the integrating factor is $e^{-ln|\cos x|} \iff \frac{1}{\cos x}$.

If we multiply in the I.G into the equation we get: $\frac{y'}{\cos x}-\frac{\sin x}{\cos^2x}y=\tan^2x$.

It is here that I run into problems. The next step would be to put: $D(\frac{y}{\cos x})=\tan^2x$

But when I controll derivate I don't get my original expression but $\frac{y'}{\cos x}+\frac{\sin x}{\cos^2x}y$

(I lose the minus sign).

Any pointers to where I went wrong would be appreciated.

$\endgroup$
1
$\begingroup$

$$\cos{x}\cdot y'=y\sin {x} + \sin^2x$$ $$\cos{x}\cdot y'-y\sin {x} = \sin^2x$$ $$\left(y\cos x\right)'=\sin^2x$$ $$y\cos x=\int\sin^2x dx=\frac{x}{2}-\frac{\sin{ 2 x }}{4}+C$$ $$y=\frac{x}{2 \cos{x}}-\frac{\sin{x}}{2}+\frac{C}{\cos x}$$

$\endgroup$
1
$\begingroup$

For the integrating factor you want to compress the left side into the form $$(e^Gy)'=e^G(y'+gy).$$ Comparing with the existing coefficients gives $$g=-\tan x=\frac{-\sin x}{\cos x}=\frac{f'(x)}{f(x)},$$ so that $$G=\ln|f(x)|=\ln|\cos(x)|.$$ But the form of the ODE with $\cos(x)y'(x)$ in the leading term is already the original equation, thus compute again $$ (\cos(x)\,y(x))'=\cos(x)y'(x)-\sin(x)y(x)=\sin^2x. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.